PREDIKSI PENGARUH HANDPHONE TERHADAP AKTIVITAS BELAJAR DENGAN METODE REGRESI LINIER (STUDI KASUS SMP PGRI 1 CIBINONG) - Nining Suryani (Jurnal Informatika dan Bisnis, 2017)
Handphone can be used as a learning tool by teachers and students in the school if the use wisely so that learning activities can be optimally implemented, for example to search and dig information in a subject but there are some students who have not been able to use the phone with good so not optimal in its use. Besides being used as a learning tool, handphone can also have negative impact for teachers and students if not used wisely. The results of data calculation by linear regression method yield r value of 0.726 which means the relationship between two variables is strong and the direction of positive value close to the number 1 perfect positive correlation. Can also be explained annova table 0.000 where 0,000 <0.005 means there is a significant influence between the influence of mobile to student learning activities. Regression equation formed that is Y = 7,372 + 0,795 X which indicate that without the influence of mobile phone at SMP PGRI 1 Cibinong hence student learning activity 7,372.Keywords: Regression. Linear. Mobile. SPSS.